Targeting the Notch signaling pathway: molecular mechanisms and therapeutic strategies for cardiac repair after myocardial infarction - Zhang, ZhiCheng; Xie, FengQun; Cheng, Jie; Liu, Xinyue; Wang, Xinran; Long, Jun; Feng, QiMao; Yuan, Dongping (Frontiers in Cardiovascular Medicine, 2025)
Myocardial infarction (MI) is a leading cause of death globally and is characterized by extensive cardiomyocyte death, fibrosis, and diminished cardiac function, leading to heart failure. The limited regenerative capacity and excessive fibrosis of the heart highlight the need for effective therapeutic strategies. The Notch signaling pathway, known for its role in cell fate determination and tissue repair, is transiently activated after MI in cardiomyocytes, endothelial cells, and smooth muscle cells. This activation modulates cardiac repair by reducing oxidative stress and apoptosis, regulating inflammation, promoting angiogenesis, and inhibiting fibrosis. Recent research has focused on targeting the Notch pathway to increase myocardial regeneration and angiogenesis via the use of gene therapy, small-molecule regulators, and cell-based therapies. For example, delivering Notch ligands through hydrogels has yielded promising results in preclinical studies, enhancing cardiac function and promoting angiogenesis. This review examines the molecular mechanisms by which Notch signaling influences cardiac repair post-MI. We also discuss its specific roles in cardiomyocyte regeneration, fibrosis inhibition, and angiogenesis enhancement. Additionally, this study evaluated the therapeutic potential of Notch pathway modulation, addressing clinical translation challenges, safety concerns, and the importance of personalized treatment strategies. Future research directions include leveraging gene editing and nanotechnology-based drug delivery to improve the efficacy and safety of Notch-targeted therapies for cardiovascular diseases.